Granulomatosis with Polyangiitis Presenting as a Parotid Gland Abscess - Blenda Dias; Daniela Soares; Patrick Sampaio; Mittermayer Santiago (Case Reports in Medicine)
Granulomatosis with polyangiitis (GPA) is a small-vessel vasculitis consisting of necrotizing granulomatous lesions in airways and focal necrotizing glomerulonephritis. However, it may affect other sites such as the skin, central nervous system, eyes, heart, gastrointestinal tract, and liver. We describe a rare case of GPA in which the initial manifestation was the involvement of the parotid gland mimicking a pyogenic abscess.